129 - MOTHER´S PERCEPTIONS OF THE INTERACTION WITH THE HEALTH PROFESSIONALS IN A NEONATE INTENSIVE CARE UNIT (Fiep Bulletin - online, 2011)
This is a qualitative study that was conducted during the months of Augsut  to October of 2008 in the Neonate Intensive Care Unit (NICU) with the objective to analyze the mothers' perceptions of the interaction  with the heatlh team when faced with the feelings and experiences when their  babies were interned in the NICU. Data were collected by means of a semi-structured interview with sevem mothers that had their babies interned in the NICU. Data were submitted to analysis of content techniques and the interprestation was based on the theoretical apports of Symbolic Interactionism and fenomenlogy of perception. The results were grouped in 3 categories? Lack of information in preparation for NICU environment, 2) Support, strength and comfort by the team: Confidence and faith in the team. They were influenced by the interaction with social milieu where they established some relations. It was found that the interaction was, the majority of times, automatical, impersonal and mechanized. There is dissatisfaction with the lack of information about their babies, and the information is incomplete, with technical language and authoritative. However, there are those that do provide attention and comfort. These are the profissionals for whome the mothers have more affection, gratidude and confidence. It is concluded that the receptivity, the interaction and the communication with the mothers were perceived as providing comfort but also lacking in personalization and in needed information about the baby's health.  The need to rethink the care model in the NICU is pointed out in order to construct strategies for the development of a dialogic relation with the mother regarding her sentiments, feelings and attitudes experienced.
Keywords: nicu; nenonatal nursing/ interaction mother/health team